La Gestión de Cobranza en la Cooperativa de Ahorro y Crédito San José del Cantón Montalvo - Llivizaca Criollo, Silvia Rossana (2017)
The Savings and Credit Cooperative San José Ltda is dedicated to grant loans and provide loan solutions to members, providing training of the respective custodian of working capital deposited daily in that entity, but in turn this activity becomes a problem to not to manage collection of credits issued causing liquidity and economic problems of the Cooperative, it is for this reason that the situation of the overdue portfolio of the Cooperative is analyzed and its recovery process from the granting of loans to customers , it is difficult for credit counselors to recover past due loans at an opportune time